Identification and characterization of a Toll-like receptor gene from Macrobrachium nipponense. Issue 108 (January 2021) - Cho, Hansam; Park, Ki Hoon; Jang, Yuyeon; Cho, Yeondong; Heo, Yoon-Ki; Kim, Minjee; Kim, Young Bong
Abstract: Outbreaks of infectious disease in shrimp pose a serious threat to shrimp agriculture worldwide. Shrimp lack adaptive immunity and depend only on innate immunity as a defense system against infectious disease. Toll-like receptors (TLR) are reported to play a critical role in the innate immune system. In this study, we identified a Toll-like receptor gene of a species of freshwater shrimp, Macrobrachium nipponense, designated MnToll, for the first time. The sequence of MnToll encoded 935 residues arranged as 10 leucine-rich repeat (LRR) domains, a leucine-rich repeat C-terminal (LRR CT) domain and a Toll/interleukin-1 receptor (TIR) domain and displayed 90% amino acid similarity to previously identified TLRs (Toll 1 and 2) of Macrobrachium rosenbergii . We additionally evaluated mRNA expression of MnToll in various tissues, including heart, gills, stomach, digestive gland, ventral nerve cord, antennal gland and muscle. Following infection with a viral pathogen, white spot syndrome virus (WSSV), MnToll expression was significantly upregulated between 12 and 72 h. Our data collectively suggest that the newly identified MnToll gene belongs to the TLR family in shrimp and is potentially involved in innate host defense, especially against WSSV. Graphical abstract: Image 1 Highlights: Identified a novel Toll-like receptor (TLR) in the freshwater shrimp species Macrobrachium nipponense. The MnToll gene showed ~90% identity with MrToll1 and MrToll2 sequences. MnToll expression was highest in gills, stomach and digestive gland. MnToll expression was highest at 12 h after WSSV infection in digestive gland and its transcription was clearly induced.